2003
DOI: 10.1002/em.10150
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of drug‐metabolizing enzymes and styrene‐induced DNA damage

Abstract: A cross-sectional study was carried out on 48 workers exposed to styrene and 14 unexposed healthy controls in order to investigate the genotoxic potential of styrene exposure. DNA damage was assessed in peripheral blood leukocytes (WBCs) by the comet assay. Polymorphisms in glutathione S-transferase genes (GSTM1, GSTT1, GSTP1) and the gene encoding microsomal epoxide hydrolase (EPHX) were characterized to assess their possible modifying role in styrene metabolism and subsequent DNA damage. Exposed workers show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 55 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…It is well known that GSTP1 enzyme takes part in the pulmonary detoxification of inhaled PAH and in oxidative stress processes (Buschini et al 2003). GSTP1 enzymes with Val105 have a seven-fold higher efficiency for PAH dihydrodiol-epoxides (Hu et al 1997) but this form is three-fold less effective using low size substrates as 1-chloro-2, 4-dimethylbenzene (Ali-Osman et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that GSTP1 enzyme takes part in the pulmonary detoxification of inhaled PAH and in oxidative stress processes (Buschini et al 2003). GSTP1 enzymes with Val105 have a seven-fold higher efficiency for PAH dihydrodiol-epoxides (Hu et al 1997) but this form is three-fold less effective using low size substrates as 1-chloro-2, 4-dimethylbenzene (Ali-Osman et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why the geneenvironment association between GSTP1 Val 105 and occupational PAH exposures from petroleum sources were significant in our study while those from wood or coal were not. Interestingly, several studies have shown that GSTP1 variants are associated with an increase in biomarkers of DNA damage when subject to high PAH-exposure environments [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Teixeira et al (2007) showed that reinforced plastics workers exposed to styrene who had mEH genotypes with low activity had more styrene oxide-hemoglobin adducts than those with high activity. However, Buschini et al (2003) using the comet assay were not able to detect differences in DNA damage in styrene-exposed workers based on mEH genotypes.…”
Section: Discussionmentioning
confidence: 76%